The Cassandra Experience: A Mixed Methods Study on the Intragroup Cognitive Dissonance of Italian Expatriates During the First Wave of COVID-19 - Di Domenico, Rossella; Cannata, Davide; Mancini, Tiziana (Frontiers in Psychology, 2021)
In March 2020, Italy was the first European country to be hit severely by the first wave of coronavirus disease 2019 (COVID-19) and to put in place moderate-high containment measures. 594 Italian expatriates participated in a cross-sectional mixed-methods survey focusing on the period that goes from the beginning of March 2020 to the beginning of April 2020. The survey aimed to describe the experiences of participants when it comes to conflicting beliefs and behavior with the Italian or host country communities in relation to COVID-19, using the Intragroup Cognitive Dissonance (ICD) framework. We explored: (1) COVID-19 risk perception (assessed for themselves, the Italian community, and the host country community); (2) COVID-19 risk meta-perception (participants’ perception of the Italian and host country communities’ risk perception); (3) intensity of emotions (assessed for themselves); (4) national group identification (assessed for themselves in relation to the Italian and host country communities) before and after the first wave of COVID-19 in Italy. An inductive thematic analysis of three open-ended questions allowed an in-depth understanding of the experiences of Italian expatriates. Results describe the ICD of participants with the Italian or host country communities, expressed as a difference between COVID-19 risk-perception and risk meta-perception. ICD predicts that when a dissonance of beliefs and behavior is experienced within an individual’s group, a shift in identification with another more consonant group will happen, if identity enhancing strategies with the dissonant group are unsuccessful. Our findings showed that when the ICD was experienced with the host country community, this was solved through a disidentification strategy and mediated by negative emotions. Identity enhancing strategies with the host country community were unsuccessfully enacted as described by the qualitative answers of participants referring to episodes of racism, ridicule, and to a Cassandra experience: predicting a catastrophic future without being believed. Unexpectedly, participants experiencing the ICD with the Italian community did not enact a disidentification strategy. An increase in virtual contacts, enhanced sense of belonging, a stronger identification baseline, and different features of the two ICDs can be responsible for these results. This study sheds light on the relevance of ICD in natural settings and on international communities, during global crises.